Extraction of fish oil from longtail tuna head waste using various method of supercritical carbon dioxide - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Nik Abdul Rahman, Norulaini; A. K. M., Omar (2013)

(untitled)
Fish oil was extracted from the head of longtail tuna (Thunnus tonggol) using various supercritical carbon dioxide (SC -C02) technique and Soxhlet method, for comparison of the yield. The extraction were performed at temperature 45 to 65 °C and pressure 20 to 40 MPa, where 65 °C/40 MPa gave the highest yield of 20.6, 35.4 and 34.1 g/ 100 g sample (dry basis) for the continuous, cosolvent, and pressure swing techniques of SC-C02, respectively. The highest C02 consumption was found in continuous technique (943.5 gN a ed by pressure swing (393.1 g), and co-solvent technique (258.6 g) respectively at 65 °C and 40 MPa. The solubility of oil in SC-C02 at co-solvent technique in¬ creased from 5.87 to 13.69 g oil/100 g of CO?, at pressure swing technique from 3.37 to 8.67 g oil/100 g of C02, and at continuous technique was only from 0.88 to 2.18 g oil/100 g of C02with the pressure and temperature from 20 to 40 MPa and 45 to 65 "C, respectively. Thus, the co-solvent method of SC-C02 was regarded as the most effective method in terms of extracting highest oil yield with least amount of C02 consumption from tuna head wastes.